Reciprocal sums

Calculus Level 5

If 1 1 + 1 1 + 2 + 1 1 + 2 + 3 + = 2 \dfrac{1}{1}+ \dfrac{1}{1+2}+\dfrac{1}{1+2+3} +\cdots = 2 , what is

1 1 2 + 1 1 2 + 2 2 + 1 1 2 + 2 2 + 3 2 + = ? \large \frac{1}{1^2} +\frac{1}{1^2 + 2^2} +\frac{1}{1^2+2^2+3^2} +\cdots =\,?

Input your answer to 3 decimal places.


The answer is 1.364.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Aug 15, 2017

We have n = 1 6 n ( n + 1 ) ( 2 n + 1 ) = n = 1 ( 6 n + 6 n + 1 24 2 n + 1 ) = n = 1 ( 6 n + 1 6 n + 24 2 n 24 2 n + 1 ) = n = 1 ( 6 n + 1 6 n ) + 24 n = 2 ( 1 ) n n = 6 + 24 ( 1 ln 2 ) = 18 24 ln 2 = 1.36447 \begin{aligned} \sum_{n=1}^\infty \frac{6}{n(n+1)(2n+1)} & = \; \sum_{n=1}^\infty \left(\frac{6}{n} + \frac{6}{n+1} - \frac{24}{2n+1}\right) \; = \; \sum_{n=1}^\infty \left(\frac{6}{n+1} - \frac{6}{n} + \frac{24}{2n} - \frac{24}{2n+1}\right) \\ & = \; \sum_{n=1}^\infty \left(\frac{6}{n+1} - \frac{6}{n}\right) + 24\sum_{n=2}^\infty \frac{(-1)^n}{n} \; = \; -6 + 24(1 - \ln2) \; = \; 18 - 24\ln2 \; = \; \boxed{1.36447} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...